Desenvolvimento, caracterização e aplicações de folhas condutoras de grafite como eletrodos de trabalho - Silva, Luiz André Juvencio (2021)
Flexible graphite sheets, graphite paper, pyrolytic graphite sheet or just graphite sheet are conductive substrates produced on a large scale for use in a wide range of applications, such as in telecommunications, lighting, computers and peripherals, power conversion and semiconductor heat generating. In this work, we show, for the first time, that commercially available graphite sheets (from different manufacturers and different thicknesses) can be used without pre-treatment for the construction of disposable electrodes with excellent performance for electroanalysis (comparable to glassy carbon electrode). Eleven different graphite sheets were evaluated by different techniques, such as scanning electron microscopy (SEM), Raman spectroscopy, cyclic voltammetry, square wave voltammetry and amperometry. The performance of the disposable devices was evaluated using the ferrocyanide ion, ferrocene, hexaamminruthenium (II) as redox probes and catechol, vanillin and metals (cadmium and lead) as model analytes. Additionally, the performance of the graphite sheet substrates was also studied for the construction of sensors modified with multi-walled carbon nanotubes. Microscopic images, the estimation of the active area and electrochemical impedance spectroscopy were the techniques selected for the characterization of the modified electrodes. The performance of these modified electrodes was evaluated using the hexaamminruthenium (II) redox probe, and dopamine and paraquat as analytes. At the end, the results obtained revealed the existence of remarkable variations among the different commercially available graphite-shaped sheets. The quality of the results obtained with graphite sheets depends on the type and origin of the material selected as the substrate (thickness, homogeneity, manufacturer). The results indicate that some graphite sheets can be a promising substitute for GCE in electroanalytical applications, as it has similar performance to this electrode, but at a cost hundreds of times lower.